Influence of feeding with fatty acids emulsions on their content in sheep wool - Motko, N. R.; Tkachuk, V. M.; Kyryliv, B. Y.; Ohorodnyk, N. Z. (Regulatory Mechanisms in Biosystems, 2025)
The feeding of sheep has a significant impact on the processes of wool formation. This especially applies to the fat comp o nents of the diet, and in particular, fatty acids. In this regard, the aim of our work was to determine the effect of feeding a water-soluble complex of fatty acids on their content in the internal lipids of the wool of Prekos ewes and lambs obtained from them. The ewes of the experimental group were fed an emulsion of fatty acids consisting of: (9E,12E)-octadeca-9,12-dienoic (С18:2ω6), (9Z)-octadec-9-enoic (С18:1ω9), hexadecanoic (С16:0), (5Z,8Z,11Z,14Z)-icosa-5,8,11,14-tetraenoic (С20:4ω6), octadecanoic (С18:0) and (9Z,12Z,15Z)-octadeca-9,12,15-trienoic (С18:3ω3). After the removal of surface lipids with carbon tetrachloride, free internal lipids of wool fibers were obtained by extraction with a chloroform/methanol mixture (2:1) in a Sox h let apparatus, and the bound ones were obtained after preliminary alkaline hydrolysis. Their fatty acid composition was studied using a gas-liquid chromatograph, after converting lipids into methyl esters by direct transesterification of fatty acids. It was e s tablished that feeding ewes with a water-soluble complex of fatty acids leads to a significant increase in free internal lipids of hexadecanoic (С16:0) acid, both in the wool of ewes and in lambs obtained from them. In the covalently bound internal lipids of wool, the content of hexadecanoic (С16:0), octadecanoic (С18:0), and (9Z)-octadec-9-enoic (С18:1ω9) acids increase d . A l though the content of (9Z)-octadec-9-enoic (С18:1ω9) acid only tend ed to increase, the amount of hexadecanoic (С16:0) acid significantly increase d in ewes from 4.29 % to 6.78%, and that of octadecanoic (С18:0) increase d in ewes from 10.62 % to 17.35%, and in lambs from 15.20 % to 19.04%. This, in turn, led to an increase in the total amount of saturated bound acids in lambs’ wool, from 84.49% in the control group to 88.37% in the experimental group. The inclusion of fatty acid emulsions in the diet of sheep, which affect the internal lipids of wool, and in particular, their fatty acid composition, can be used to improve the physical, and therefore technological characteristics of wool raw materials.